2022
DOI: 10.3390/biology11091370
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Transcranial Direct Current Stimulation over the Primary Motor Cortex in Improving Postural Stability in Healthy Young Adults

Abstract: Transcranial direct current stimulation (tDCS) over the primary motor cortex (M1) is of increasing interest to improve motor performance in healthy adults and patients with respective deficits. This study aimed to examine whether tDCS over M1 can improve static and dynamic postural stability in young healthy adults. Seventeen healthy participants (mean age = 25.14 ± 2.50 (standard deviation, SD) years) received sham and anodal tDCS (2 mA) over the vertex at the Cz electrode position for 15 min. Static and dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 58 publications
1
3
0
Order By: Relevance
“…Our findings are in line with previous findings that a-tDCS over M1 improved postural stability by reducing the center of pressure sway area (Hou et al, 2022). tDCS may modulate factors relevant to maintaining postural stability, as muscle stiffness, ankle proprioception, and motor cortex excitability (de Moura et al, 2019).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings are in line with previous findings that a-tDCS over M1 improved postural stability by reducing the center of pressure sway area (Hou et al, 2022). tDCS may modulate factors relevant to maintaining postural stability, as muscle stiffness, ankle proprioception, and motor cortex excitability (de Moura et al, 2019).…”
Section: Discussionsupporting
confidence: 93%
“…A study by Kaminski et al, (2016) revealed that 20 minutes of anodal (a)-tDCS bilaterally over M1 leg area during a balance task was effective in facilitating dynamic balance task (DBT) learning in YA. A recent study by Hou et al (2022) further examined the offline effect and showed that one single session of a-tDCS over M1 could decrease the center of pressure (CoP) sway area and improve postural stability in healthy YA. Notably, a systematic review (Halakoo et al, 2023) showed that both a-tDCS and cathodal (c-)tDCS over M1 can vary in their effects on posture and balance, contingent on the study population.…”
Section: Introductionmentioning
confidence: 99%
“…The Cz region usually covers bilateral lower-limb area of M1 (Mizuno and Aramaki, 2017). Studies have shown that tDCS targeting the Cz region can modulate the activity of M1, thereby influencing motor control and coordination (Park et al, 2019;Hou et al, 2022). The HD-tDCS consisted of 20-min stimulation of current intensity of 2 mA (Workman et al, 2020a;Workman et al, 2020b).…”
Section: Hd-tdcs Protocolmentioning
confidence: 99%
“…Based on M1 as primary motor area can encode motor execution [ 5 ],tDCS applied bilaterally to the M1 motor cortex has been shown to increase knee flexor and extensor strength in healthy males on the non-dominant side [ 6 ]. In addition, Hou et al [ 6 ] showed that anodal tDCS can instantly improve the static and dynamic balance ability of the healthy young people standing on one leg as well as jumping over a 10 cm obstacle [ 7 ]. This potentially indicates that the use of tDCS may potentially enhance dynamic balance ability in daily living setting environment involving with multiple crossing and jumping abilities.…”
Section: Introductionmentioning
confidence: 99%